Characteristics of severe life events, attachment style, and depression – Using a new online approach - Bifulco, A; Kagan, L; Spence, R; Nunn, S; Bailey-Rodriguez, D; Hosang, G; Taylor, M; Fisher, HL (Wiley, 2019)
Objectives Severe life events are established as provoking agents for depression in combination with vulnerability factors. Identifying features of severe events improves the prediction of disorder but are rarely utilized, mainly because life event research is increasingly dominated by self‐report checklists with no capacity for inferring such characteristics. This paper investigates the association of severe life events’ features with depression and insecure attachment styles using a new online measure of life events in a clinical and control sample.